The Significance of Sámi Rights : Law, Justice, and Sustainability for the Indigenous Sámi in the Nordic Countries - Cambou, Dorothée; Ravna, Øyvind (Taylor and Francis, 2023)
This book examines the significance of the rights of the Sámi people and analyses the issues raised by the recognition and implementation of these rights in the Nordic countries. Written together by Sámi and non-Sámi experts, the book adopts a human rights approach to examine the adequacy of law and policies that seek to protect the culture and livelihood of Sámi communities in their traditional lands and territories. The book discusses contemporary legal and jurisprudential developments in the field of Sámi rights. It examines the processes and challenges in the recognition and implementation of these rights, particularly in relation to the governance of their traditional land and resources. The book will be of particular interest to legal scholars, political scientists, experts in the field of Indigenous peoples’ rights, governmental authorities, and members of Indigenous communities. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons (CC-BY) 4.0 license.